A postmortem study on the volume of the human adrenal glands (Bangladesh Journal of Medical Science, 2013)
Objective: A Cross-sectional descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, to see the variation in the volume of the adrenal glands with age in Bangladeshi people. Materials & Methods: The study was performed on 140 post mortem human adrenal glands collected from 70 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four age-groups including group A (11-20 years), group B (21-30 years), group C (31-40 years) & group D (41-60 years). The length, breadth and thickness of each adrenal gland were measured by using a slide calipers. Then the volume of each adrenal gland was determined by the product of its length, breadth and thickness multiplied by 0.52, according to the prolate ellipsoid formula. Results: The mean volume of the right adrenal glands were found 6.36±0.85 cm3 in group A (11-20 years), 6.49±0.76 cm3 in group B (21-30 years), 6.50±0.80 cm3 in group C (31-40 years), 6.76±0.79 cm3 in group D (41-60 years). The mean volume of the left adrenal glands were found 6.97±1.02 cm3 in group A (11-20 years),6.93 ±0.83 cm3 in group B (21-30 years), 6.65±0.79 cm3 in group C (31- 40 years), 7.09±0.81 cm3 in group D (41-60 years). The differences between the right and left adrenal glands and the difference between age groups were not statistically significant. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 282-285 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15425